Modification of the circadian rhythm of onset of acute myocardial infarction by long-term antianginal treatment. Issue 11 (November 1992) - Woods, Kent L; Fletcher, Susan; Jagger, Carol
Abstract : Objective —To elucidate the mechanism of the circadian pattern of onset of acute myocardial infarction by examining the effects of prior antianginal treatment upon it. Design —Retrospective analysis of clock time of the onset of acute myocardial infarction by linear modelling to define the circadian distribution of hourly onset rates and to examine the deviation of treated groups of patients from this distribution. Setting —Coronary care unit in a general hospital taking unselected acute admissions from a district of 0·9 million people. Patients —A series of 2231 patients with confirmed acute myocardial infarction. Results —A major 24 h cycle and smaller 12 h and 6 h cycles were present in patients not taking antianginal medication. Onset rates varied twofold over the day, with maxima around 10.00 am and 10.00 pm. This pattern was unchanged in patients on prior treatment with regular nitrates, but in those who had been taking a β blocker or a calcium antagonist the 24 h cycle was absent. Conclusions —These results are best explained by the shared property of β blockers and calcium antagonists to reduce blood pressure and myocardial oxygen demand. The mid-morning peak of the onset of myocardial infarction is attributable to the physiological increase in sympathetic drive and cardiac work at that time. The data are not consistent with the triggering of the 24 h periodicity by fluctuations in coronary tone or haemostatic activity.